2014
DOI: 10.1515/jpm-2013-0289
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan fasting and pregnancy: implications for fetal development in summer season

Abstract: We demonstrated some adverse effects of Ramadan fasting on fetal development. In the Islamic religion, pregnant individuals have the privilege of not fasting; therefore, they should consider postponing fasting to the postpartum period, especially in the summer season. If they are willing to do so, an appropriate nutritional program should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…Moradi reported that fasting did not influence amniotic fluid amount, whereas Sakar et al ., showed that AI was increased in nonfasting pregnant women and Seckin et al ., displayed that it decreased in fasting people. [ 15 16 17 ] In line with these studies, we noticed that fasting – regardless of season – did not change Doppler indices including resistive index, pulsatility index, and systolic/diastolic ratio of umbilical artery, middle cerebral artery, and uterine artery associated with fetomaternal circulation. However, its effect on AI was different, especially in summertime studies.…”
Section: Discussionsupporting
confidence: 76%
“…Moradi reported that fasting did not influence amniotic fluid amount, whereas Sakar et al ., showed that AI was increased in nonfasting pregnant women and Seckin et al ., displayed that it decreased in fasting people. [ 15 16 17 ] In line with these studies, we noticed that fasting – regardless of season – did not change Doppler indices including resistive index, pulsatility index, and systolic/diastolic ratio of umbilical artery, middle cerebral artery, and uterine artery associated with fetomaternal circulation. However, its effect on AI was different, especially in summertime studies.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, other potential effects of Ramadan fasting may not have been included in our outcome measures. Other studies have shown effects of Ramadan fasting on fetal movement [ 41 ], maternal glucose levels [ 42 ] and various fetal growth indices [ 43 ]. Furthermore, our review did not examine whether fasting in the periconceptional period was associated with pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…4 In another study from a country where the Islamic month was observed during summer season (July-August), investigators found a decrease in the amniotic fluid volume among fasting pregnant mothers, when compared to non fasting mothers. 5 Karateke A et al, in a cohort of more than 200 women, also did not find any significant difference in the growth parameters of fetus among fasting and non fasting women, except increase in amniotic fluid and maternal weight gain amongst women who fasted during second trimester. 6 In another prospective cohort study from Netherlands, women who fasted during the first trimester had lighter weight newborns, compared to non fasting women (-198 g, 95% CI -447, 51, P= 0·12), but this was not found statistically significant.…”
Section: Introductionmentioning
confidence: 88%